Forming Ability of Ultrafine‐Grained Aluminum Plates Processed by Incremental Equal Channel Angular Pressing. Issue 10 (8th August 2019) - Ciemiorek, Marta; Bartkowski, Piotr; Chromiński, Witold; Olejnik, Lech; Lewandowska, Małgorzata
Abstract : Recently, post‐severe plastic deformation (SPD) shaping processes have attracted attention because of the limited amount of data available on this topic. Herein, the formability of commercially pure aluminum plates with an ultrafine‐grained microstructure processed by incremental equal channel angular pressing (I‐ECAP) up to eight passes is discussed. The formability is evaluated experimentally using a cup‐forming operation followed by modeling using finite element method (FEM). The drawn cups made of ultrafine‐grained aluminum exhibit a smooth surface and show no signs of planar anisotropy (no earing). It is thus demonstrated that I‐ECAP processing is successful in terms of reducing the anisotropy and may be an attractive process for obtaining a material suitable for forming sheet metal. Abstract : The formability of commercially pure aluminum plates with an ultrafine‐grained microstructure processed by incremental equal channel angular pressing is discussed. It is proven that this processing is advantageous for obtaining a material suitable for forming sheet metal. The drawn cups made of ultrafine‐grained aluminum exhibit a smooth surface and show no signs of planar anisotropy (no earing).